The Determinants of Private Tutoring Participation for Mathematics in China: Focusing on the Role of Student Metacognition - Zhang, Yuhuan; Ma, Xiao; Wang, Lidong (Frontiers in Psychology, 2020)
Participation in private tutoring has been a global educational phenomenon and is especially prevalent in China. The present study conducted a student-report questionnaire and collected school reports of mathematical achievement to track a year of the longitudinal variation of private tutoring and obtained an analysis of the impact of metacognition on private tutoring participation and its moderating effects between environment-related and initial indicators and mathematical private tutoring participation. The empirical results of this study showed that metacognitive level for learning process monitoring, family economic condition, and mathematics achievement could impact the decision to participate in private tutoring. The results also showed that family economic condition could moderate the effect of metacognitive level for learning process monitoring on the decision to participate in private tutoring. Practical implications for educational competent department and the schoolteachers were discussed.